THE IMPACT OF MICRO AND SMALL INDUSTRIES, INFLATION, AND OPEN UNEMPLOYMENT ON ECONOMIC GROWTH IN GRESIK REGENCY (2021-2023) - Zerlindah, Clairina Cathliniyah; Sahliyah, Fatihatus; Harahap, Syamsir Alamsyah (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to analyze the effect of micro and small industries, inflation, and open unemployment on economic growth in Gresik Regency. Economic growth is an important indicator in measuring the success of regional development, so understanding the factors that influence it is very important for the formulation of appropriate policies. This type of research is quantitative research with an explanatory approach. The data used is secondary data in the form of annual data from 2021 to 2023 obtained from the Gresik Regency Statistics Agency. The analysis methods used are descriptive statistics, multiple linear regression, coefficient of determination, classical assumption test and hypothesis testing. The results showed that the growth of micro and small industries was found to have a positive, but statistically insignificant effect on economic growth. Meanwhile, inflation and open unemployment have a negative significant effect on economic growth in Gresik Regency. These findings indicate the importance of developing the micro and small industry sector as well as controlling inflation and unemployment to support sustainable economic growth in Gresik Regency.